2018
DOI: 10.1016/j.cell.2018.10.038
|View full text |Cite|
|
Sign up to set email alerts
|

Defining T Cell States Associated with Response to Checkpoint Immunotherapy in Melanoma

Abstract: SUMMARY Treatment of cancer has been revolutionized by immune checkpoint blockade therapies. Despite the high rate of response in advanced melanoma, the majority of patients succumb to disease. To identify factors associated with success or failure of checkpoint therapy, we profiled transcriptomes of 16,291 individual immune cells from 48 tumor samples of melanoma patients treated with checkpoint inhibitors. Two distinct states of CD8+ T cells were defined by clustering, and associated with patient tumor regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

78
1,536
10
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,449 publications
(1,752 citation statements)
references
References 69 publications
78
1,536
10
6
Order By: Relevance
“…Glucocorticoids can be produced in the TME and combine with the immune suppressive cytokine IL-27 to form an immunoregulatory circuit that promotes gene programs associated with CD8 + T cell dysfunction. The relevance of glucocorticoid signaling pathways to human cancer is supported by our observation that increased steroidogenic capacity in the TME correlated with decreased survival and that high expression of the glucocorticoid + IL-27 signature in the CD8 + TILs of melanoma patients correlated with failure to respond to checkpoint blockade therapy (Sade-Feldman et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Glucocorticoids can be produced in the TME and combine with the immune suppressive cytokine IL-27 to form an immunoregulatory circuit that promotes gene programs associated with CD8 + T cell dysfunction. The relevance of glucocorticoid signaling pathways to human cancer is supported by our observation that increased steroidogenic capacity in the TME correlated with decreased survival and that high expression of the glucocorticoid + IL-27 signature in the CD8 + TILs of melanoma patients correlated with failure to respond to checkpoint blockade therapy (Sade-Feldman et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…To examine the relevance of glucocorticoid + IL-27 signaling in human disease, we scored the glucocorticoid + IL-27 signature in the single-cell data of TILs from melanoma patients preand post-treatment with checkpoint blockade (Sade-Feldman et al, 2018). We found that the glucocorticoid + IL-27 signature scored highly in CD8 + TILs that also scored highly for the T cell dysfunction signature (Figure 5f, panels V and VI).…”
Section: Glucocorticoid and Il-27 Signaling Co-operate To Promote Cd8mentioning
confidence: 98%
“…It was noted on pathology that 15% of nucleated cells in the periphery and 5% of cells in the center were CD8‐positive lymphocytes. Although the significance of this observation is unclear, preliminary data demonstrate better outcomes for patients who have increased CD8 infiltration of their melanoma …”
Section: Case Presentation and Overviewmentioning
confidence: 99%
“…The purity evaluation could therefore eliminate such misleading conclusions, potentially aiding our understanding of cellular function, state and behavior. While pioneering approaches such as silhouette 7 , DendroSplit 8 , and distance ratio 9 have been devoted to determining the optimal number of identified clusters by calculating the ratio of within-cluster to inter-cluster dissimilarity, they are not comparable among datasets and have poor interpretability of cluster purity. For example, an average silhouette value of 0.7 indicates a fairly strong consistency for a given cluster, but it is still unknown whether this cluster is a pure population or a mixture of similar subpopulations especially when frequent dropout events occur.…”
Section: Introductionmentioning
confidence: 99%